Release of pollutants in MBT landfills: Laboratory versus field. (June 2020) - Molleda, Ancella; López, Ana; Cuartas, Miguel; Lobo, Amaya
Abstract: The evolution of liquid pollutants over time remains one of the main issues in a landfill for decades. However, although the literature contains several works that attempt to model the release of pollutants from waste, there is still scant information on the matter, especially for MBT waste. In this study, contaminant washing laboratory tests and field trials have been carried out on different waste particle sizes and fractions to estimate to what extent the former provide adequate information about the evolution of the leachate in a real MBT waste landfill. The results show significant differences between the test results. The majority of inorganic contaminants (Ca, Cu, Mg, Na, Ni, Zn), however, complex with organic matter in all percolation column tests. The use of other materials, the early beginning of the methanogenic phase, and the increase in pH and temperature in the field alter the reactions and, importantly, the leaching of some of the components that precipitate, such as Ca, Fe and Mg, or NH4 –N, which increases its presence. It is therefore necessary to adapt the models and the current test standards to assess the fate of biodegradable waste such as MBT under field conditions. Highlights: The size and fraction of tested waste alter the laboratory results. Complexation between inorganic and organic compounds determine leachate composition. The concentration of pollutants and their release vary from laboratory to field. Biodegradation and pH precipitate Ca, Mg and Fe and increase NH4 –N in landfill. Current models and standards should be adapted to MBT and consider biodegradation.